Teachers’ experience with early intervention services for students with Autism Spectrum Disorder - Alhazmi, Rawan A.; Alzahrani, Hassan M. (Frontiers in Education, 2025)
The current research aimed to assess the experience of teachers of children with Autism Spectrum Disorder (ASD) in providing early intervention services and determine these teachers’ recommendations to help improve services. The qualitative research methodology utilized the narrative method to achieve the objectives of the research. Data was also collected through semi-structured individual interviews, and the research sample consisted of six teachers working with children with ASD in early childhood. The results indicated teachers of children with ASD are knowledgeable regarding ASD and early intervention services. The results also indicated that teachers face many challenges when providing early intervention services to children with ASD. The results demonstrated the need for ASD teachers to receive training courses and exchange experiences with ASD teachers, as well as the need to activate family participation by providing awareness and reinforcement. The results also revealed the need to provide integrated services within the center, add learning through play, and also create an effective educational environment for children with ASD. Recommendations were also provided, based on the findings of the research.